IMPACT OF CORE SATURATION ON OPERATING CHARACTERISTICS OF THREE-PHASE SQUIRREL CAGE MOTOR (ETIMA, 2024)
The induction motors are considered to be the largest electricity consumers worldwide. Therefore, the exact calculation of their operating characteristics in various operating modes is important for determining their operation, electricity consumption and the various types of losses that occur during their operation that have the considerable impact on efficiency of the motors. Paper analyses two models of three-phase squirrel cage induction motor, modeled in Simulink. The first model is considered to have linear magnetizing characteristic while in the second model the core saturation is taken into account by introducing the non-linearity of the magnetization characteristic. The models are analyzed with fifteen percent increased voltage which shifts the operating point into the saturated part of magnetizing characteristic for the saturated model. The impact of core saturation on motor current, speed and torque is observed. The obtained results of the transient characteristics from Simulink are compared with data of current and torque from steady-state models. The core saturation increases the motor current, losses and decreases the motor efficiency. The areas where the core saturation occurs, mainly located in stator teethes, are also observed in Finite Element models (FEM). The derived models contribute to the better understanding of effect of core saturation and its impact on motor operation, thus providing the guidelines for the motor designers.